STRATEGI PEMASARAN MAKE UP ARTIST NGANJUK DALAM PERSAINGAN UNTUK MENINGKATKAN MINAT KONSUMEN - Khiftiyah, Fattma Ainun; Meilina, Restin; Damayanti, Susi (Universitas Nusantara PGRI Kediri, 2025)
This study aims to examine the marketing strategy of traditional bridal makeup service providers in Nganjuk, by emphasizing the use of local cultural values ​​as a competitive advantage. The method used is a qualitative approach with case studies, data collected through interviews, observations, and documentation, and analyzed using the SWOT model. The results of the study indicate that the application of local culture in marketing strategies can strengthen business positions and attract consumer interest amidst tight competition. The novelty of this study lies in the emphasis on preserving Javanese cultural values ​​as a differentiation strategy in the modern service industry, which is still rarely explored in depth in bridal service marketing studies. These results provide practical and theoretical contributions to the development of culture-based businesses in the future.